Transformasi Digital Native menjadi Wirausahawan Digital: Determinan Niat Berwirausaha Generasi Z - Andressa Noviar Azhari; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the factors influencing entrepreneurial intention and capability among Generation Z in addressing the challenges of educated unemployment, technological disruption, and the dynamics of the digital economy. The research employs a systematic literature review approach by examining scholarly articles published between 2020 and 2025 retrieved from reputable academic databases. Literature selection was conducted based on inclusion and exclusion criteria emphasizing relevance to the determinants of Generation Z’s entrepreneurial intention and methodological rigor. The synthesis results indicate that entrepreneurship education, family support, self-efficacy, and digital literacy are key factors that significantly influence entrepreneurial intention and capacity. Entrepreneurship education emerges as the most dominant predictor, particularly when combined with practice-based learning. Family support strengthens self-confidence and entrepreneurial orientation. Self-efficacy acts as a mediator between entrepreneurial knowledge and entrepreneurial intention, while digital literacy enhances technical readiness to leverage technology for business development.Overall, fostering entrepreneurship among Generation Z requires a holistic approach that integrates educational, psychological, digital competency, and environmental support aspects to encourage consistent and sustainable entrepreneurial activities.